Analisis Yuridis Penerapan Restoratif Justice pada Tahap Penuntutan Terhadap Tindak Pidana Pencurian Di Bawah Nilai Dua Juta Rupiah Dalam Sistem Hukum Di Indonesia - Purba, Ahmad Rusly (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
Indonesia continues to strive for laws that are implemented or lived for the community to be sourced from the values that live and develop in society, legal entities in Indonesia if applied then the community will not feel objections or unfamiliar with the legal model. Restorative justice is the resolution of criminal cases by involving perpetrators, victims, families of perpetrators / victims, and other related parties to jointly seek a fair solution by emphasizing recovery back to its original state, and not retaliation. Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Attorney General of the Republic of Indonesia states that one of the powers of the Attorney General is to set aside cases in the public interest. The AGO feels that there are many irregularities in the criminal law system that has been in effect, therefore in this case what is meant by "public interest" is the interest of the nation and state and / or the interests of the wider community. This research was conducted using a research method in the form of a Normative Juridical method. The data collection is done by means of literature study. The research specification used is descriptive qualitative. This study aims to determine how restorative justice against minor offenders in the form of theft at the prosecutor's level and how the implementation of restorative justice against minor offenders in the form of theft at the Pangkalpinang District Attorney's Office studies the case of Termination of Prosecution through the Decree of Termination of Prosecution of the Pangkalpinang Kajari Number 01/L.9.10.3/Eoh.2/01/2022 dated January 13, 2022. Keywords: Theft; Termination of Prosecution; Restorative Justice